PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH, DAN DANA PERIMBANGAN TERHADAP BELANJA MODAL - Santoso, Erna; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Reformation has brought changes to the form of government in Indonesia, which in the beginning it wascentralization now it becomes decentralization structure. The local government is given wide rights andauthorization to manage their own local business and the local government is required to maximize their localpotential to fulfill their local expenditure including the capital expenditure. Therefore, this research is meant totest whether the economic growth, local own source revenue, and Balance fund give influence to the capitalexpenditure to the districts / cities in East Java. The population is all the districts / cities in East Java and thesecondary data and the sample collection technique has been carried out by using purposive sampling method.Based on the predetermined criteria 108 from 36 districts / cities in East Java, with the observation term is 3years from 2013 to 2015 have been selected as samples. The analysis method has been conducted by usingmultiple linear regressions analysis and the application instrument of Statistical Product and Service Solutions(SPSS). The result of this research shows that economic growth does not have any influence to the capitalexpenditure. Meanwhile, local own source revenue and balance fund has positive influence to the capitalexpenditure. Simultaneously, the independent variables have significant influence to the dependent variable withits significance level is 0,000.Keywords: Economic growth, Local own source revenue, balance fund, capital expenditure.